Chainsaw Operator Training & Occupational Safety and Health Socialization at Perum Perhutani KPH Banyuwangi Utara - Ikhwanul Qiram; Joko Suwondo (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
Chainsaw operator is an important profession in logging production forest which has high occupational accident risk criteria. These potential risks can be in the form of accidents that are mechanical, electrical, biological, and physical. This community service activity is in the form of socializing chainsaw machine operational SOPs and introducing occupational health and safety as a preventive effort in reducing the potential risks faced by loggers in the Perum Perhutani KPH Banyuwangi Utara. This activity received quite a good appreciation for chainsaw operators in the Perum Perhutani KPH North Banyuwangi environment. The results of the training have provided basic knowledge about maintaining chainsaw machines and increasing safety first discipline for all parties involved in chainsaw operator activities.